Stress Memory and the Inevitable Effects of Drought: A Physiological Perspective - Fleta-Soriano, Eva; Munné-Bosch, Sergi (Frontiers in Plant Science, 2016)
Plants grow and develop by adjusting their physiology to changes in their environment. Changes in the abiotic environment occur over years, seasons and days, but also over minutes and even seconds. In this ever-changing environment, plants may adjust their structure and function rapidly to optimize growth and reproduction. Plant responses to reiterated drought (i.e. repeated cycles of drought) differ from those to single incidences of drought; in fact, in nature, plants are usually exposed to repeated cycles of drought that differ in duration and intensity. Nowadays, there is increased interest in better understanding mechanisms of plant response to reiterated drought due, at least in part, to the discovery of epigenomic changes that trigger drought stress memory in plants. Beyond epigenomic changes, there are, however, other aspects that should be considered in the study of plant responses to reiterated drought: from changes in other "omics" approaches (transcriptomics, proteomics and metabolomics), to changes in plant structure; all of which may help us to better understand plant stress memory and its underlying mechanisms. Here, we present an example in which reiterated drought affects the pigment composition of leaves in the ornamental plant Silene dioica and discuss the importance of structural changes (in this case in the photosynthetic apparatus) for the plant response to reiterated drought; they represent a stress imprint that can affect plant response to subsequent stress episodes. Emphasis is placed on the importance of considering structural changes, in addition to physiological adjustments at the "omics" level, to understand stress memory in